Composites manufacturing : materials, product, and process engineering - Mazumdar, Sanjay K. (CRC Press, 2002)
Annotation Mazumdar draws on his experiences as an author, lecturer, educator, and head of a service-oriented company providing various products to the composite materials industry, in writing this textbook on composites manufacturing. The book takes the reader step-by-step from raw material selection to final part fabrication and recycling. Specific chapter topics include raw materials for part fabrication, material selection guidelines, product development, design for manufacturing, manufacturing techniques, process models, production planning and manufacturing instructions, joining of composite materials, machining and cutting of composites, cost estimation, and recycling of composites. The text is suitable for students, engineers, and researchers working in the composite materials field. Annotation c. Book News, Inc., Portland, OR (booknews.com).
Keywords: Composite materials.; elektronické knihy; electronic books